2000
DOI: 10.1111/j.1834-7819.2000.tb00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of dental trauma: A review of the literature

Abstract: This article reviews recent reports describing the aetiology of dental trauma from national and international studies as well as the different classifications currently used to report dental injuries. It also discusses possible preventive measures to reduce the increasing frequency of dental trauma. Reported studies demonstrate that males tend to experience more dental trauma in the permanent dentition than females, however, there does not appear to be a difference between the sexes in the primary dentition. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

57
399
12
41

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(521 citation statements)
references
References 27 publications
(67 reference statements)
57
399
12
41
Order By: Relevance
“…This finding is in accordance with reports from different authors who found high frequencies of crown fractures in falls and collisions. [10][11][12][13][14][15][16] Avulsions were mostly observed in the maxilla, as found in other studies. [17][18][19][20][21][22] Lateral dislocations were found in the anterior segments of both jaws.…”
Section: Lieger Et Al Dental Injuries and Facial Fractures J Oral Msupporting
confidence: 56%
“…This finding is in accordance with reports from different authors who found high frequencies of crown fractures in falls and collisions. [10][11][12][13][14][15][16] Avulsions were mostly observed in the maxilla, as found in other studies. [17][18][19][20][21][22] Lateral dislocations were found in the anterior segments of both jaws.…”
Section: Lieger Et Al Dental Injuries and Facial Fractures J Oral Msupporting
confidence: 56%
“…There is a lack of consensus on an appropriate definition and classification of dental trauma. [24][25] We used the O'Brien 15 criterion, which has been employed in previous Brazilian studies. [26][27][28] Thus, it allowed for proper comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the orofacial trauma data available in the literature has been collected retrospectively from cross-sectional studies or from longitudi- nal studies of patient records. [1][2][3][4][5][6][7] In the current study, the assessment of standardized trauma records with information collected at the time of assistance enables the authors to obtain more reliable data relative to previous retrospective studies in which injuries were only registered if signs and/or symptoms were evident at the time of examination.…”
Section: Discussionmentioning
confidence: 95%
“…The great variation may be due to a number of different factors such as the trauma classification, and geographical and behavioral differences between study locations and countries. [7] This study evaluated orofacial trauma and injuryassociated factors in children who visited an emergency department. A total of 1296 children in 12055 patients with orofacial trauma from 0 to 18 years of age were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation